Gross job flows and determinants of job creation: The case of large firms in Turkish manufacturing - ÖZERKEK, YASEMİN (BILGESEL YAYINCILIK SAN & TIC LTD, 2011)
The analysis of gross job flows in the labor market has become an issue of great interest in the literature. The Turkish economy, which adopted a more outward-oriented economic development strategy in the beginning of 1980s, attracts attention to study its job flow dynamics. To this end, this study analyzes the employment dynamics of the largest private industrial firms of Turkey during 1980-2006 and investigates the determinants of job creation. The findings show that; (i) there exist both job creation and job destruction in all phases of the business cycle, (it) crises (booms) are times of high (low) job destruction and low (high) job creation, (iii) gross job creation is slightly more variable than gross job destruction over the cycle, (iv) these firms are heterogeneous in their employment behavior (v) their job reallocation process is long-term in nature, and (vi) domestic sales and export of these firms have positive effect on their job creation.
Keywords: Job creation; Job destruction; Largest industrial firms in Turkey; DESTRUCTION